Assessing Perceived Healthcare Access and Attitudes Towards Complementary and Alternative Medicine Amongst Parents in Cebu City - Gonzales, Ma. Bianca; Prescillas, Alyssa Belle; Chavez, Kyla Angela; Relacion, Justine Rose; Lawas, Alexandre Louise; Gagani, Flordeliza (Newinera Publisher, 2024)
With the pressing demands of healthcare for most families, especially parents, different perceptions and challenges can be drawn when accessing healthcare needs and services, which can potentially drive people to generate certain attitudes towards alternative treatments or CAM in addressing health disparities. Hence, this study aimed to measure the perceived healthcare access and attitudes towards complementary and alternative medicine (CAM) among randomly selected fifty parents in a mountainous barangay in Cebu City, Philippines through a descriptive correlational approach. Data were collected using two valid and reliable 5-point adapted Likert-type survey questionnaires. Findings revealed that perceived healthcare access was rated average, while attitudes towards CAM were high. The variables were also not found to be significant r (48) = -.057, p = .694189, p > 0.05 at a = 0.05, thus accepting the null hypothesis of no significant relationship, and concluding that there is a weakly negative correlation (r = -.057) between the perceived healthcare access and attitudes towards CAM among the parents. This means that the views of parents regarding the availability and access to healthcare services do not entirely but can weakly influence their positive outlook towards alternative medicines and treatments, as it could potentially come from other factors such as inherited tradition, socio-cultural influence, preference, and prior experience of efficacy. This negative relationship suggests that limited healthcare access leads to more prominent use of alternative medicines, and vice versa. This study recommends implementing policy changes, emphasizing the need to improve access to services in low-income areas, especially in mountainous barangay.